THE SACRED VALUE OF DEATH IN UM DOCE AROMA DE MORTE, FROM GUILLERMO ARRIAGA - Bárbara Cristina Marques (Travessias, 2009)
Guillermo Arriaga, fiction and screen writer seems to demonstrate a deep interest in Death as an important theme all over his work. We can verify it in films such as Amores Brutos (2000), 21 gramas (2003) and Babel (2006), but especially in his last novel published in Brazilnamed Um doce aroma de morte (2007). Using the countryside of Mexico, an arid and miserable region as the scenario for his story, the author demonstrates the way death can become something sacred. Death in Um doce aroma de morte appears in his narrative as a construction that uses the limit as its main element, manifested in situations where a curious contemplation of the livid, naked and aromatic body of Adela emerges. The bad smell and the degradation of the body that serve as evidence for the physical death are diluted in the bittersweet floral smell that gives off from Adelas body. In this way, thinking Death as a sort of leit motiv in the Arraigas narrative we purpose to understand it in two different movements: The ritual that involves the deaths